Analisis penerapan model pembelajaran Teams Games Tournament (TGT) pada materi perkalian siswa kelas III sekolah dasar - Anindyana, Kholifah; Daryanto, Joko; Kurniawan, Sandra Bayu (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2023)
This study aims to analyze the application of the Teams Games Tournament (TGT) learning model to the multiplication of grade III students. About the implementation of learning, model syntax, and interaction and interest in learning multiplication. The research subjects were teachers and third grade students. This research is a descriptive qualitative research based on field phenomena. Data collection techniques used are observation, interviews, and documentation. Data validity is used with data triangulation techniques. The analysis technique used is the data analysis technique of Miles and Huberman. The results of this study indicate that the teacher has carried out learning through the application of models very well. Teachers have implemented innovative learning with the TGT model, through student-centered learning, contact of view, active involvement of students, enthusiasm and interest in learning, and good interaction. The problem is solved by using an innovative tgt type model. Teachers have long used the tgt model to learn multiplication, adapting the 2013 curriculum and innovative learning. So that it can be seen that the success in applying the tgt model to understanding, interest in learning and multiplication learning outcomes of students at SDN Pondok is quite good.